2003
DOI: 10.1046/j.1365-2249.2003.02071.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 10 induced augmentation of delayed-type hypersensitivity (DTH) enhances Mycobacterium bovis bacillus Calmette-Guérin (BCG) mediated antitumour activity

Abstract: SUMMARYIntravesical BCG therapy is effective in the treatment of superficial bladder cancer. Both clinical and experimental results suggest a role for cytokines and delayed-type hypersensitivity (DTH) in BCGinduced antitumour immunity. We characterized the modulatory effects of BCG on bladder cytokine expression and determined the relationship between DTH and BCG antitumour activity. The bladders of mice were instilled with BCG through a catheter. Bladder tissue RNA and urine were collected for evaluation of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 47 publications
2
73
0
Order By: Relevance
“…Thus, it is proposed that efforts to polarise the immune response by increasing the production of Th1-promoting IL-12, and diminishing IL-10 will have a therapeutic value. Indeed, IL-10 deletion studies performed either by antibody inhibition or using gene knockout animals resulted in enhanced DTH response and antitumour activity (Nadler et al, 2003), while IL-10 knockout mice also showed prolonged survival and response in a syngeneic model of orthotopic bladder cancer (Riemensberger et al, 2002). This response was shown to coincide with an increased influx of T and NK cells into the bladder walls of these mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is proposed that efforts to polarise the immune response by increasing the production of Th1-promoting IL-12, and diminishing IL-10 will have a therapeutic value. Indeed, IL-10 deletion studies performed either by antibody inhibition or using gene knockout animals resulted in enhanced DTH response and antitumour activity (Nadler et al, 2003), while IL-10 knockout mice also showed prolonged survival and response in a syngeneic model of orthotopic bladder cancer (Riemensberger et al, 2002). This response was shown to coincide with an increased influx of T and NK cells into the bladder walls of these mice.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the production of immunosuppressive IL-10 during BCG therapy reduces inflammation and the anticancer response (Nadler et al, 2003). On this basis, we postulate that the immune response elicited by BCG is suboptimal and potentially antagonistic, and might limit the survival of some patients with bladder cancer.…”
mentioning
confidence: 95%
“…These cells produce IFN-g, but not IL-4. Bacillus Calmette-Guérin therapy-related research has revealed an increased CD1 expression of TCC cell lines in the presence of live BCG (Ikeda et al, 2002) and a virtual absence of urinary IL-4 during BCG treatment (Nadler et al, 2003). Accordingly, it is tempting to hypothesise that CD1-facilitated BCG antigen presentation contributes to the development of BCG immunity.…”
Section: Cytotoxic Effects Of Bcg On Bcg-internalising Urothelial Cellsmentioning
confidence: 99%
“…These infiltrating leukocytes, together with activated urothelial cells, produce numerous proinflammatory cytokines and chemokines. Subsequently, a transient massive amount of cytokines and chemokines (Bohle et al, 1990b;Boer et al, 1991a;De Reijke et al, 1996;Taniguchi et al, 1999;Saint et al, 2002;Nadler et al, 2003;Luo et al, 2007), together with a variety of leukocyte types (Boer et al, 1991a-c;Simons et al, 2008), can be detected in voided urine. The urine of mice treated with intravesical BCG also exhibits increased concentrations of cytokines and chemokines (Saban et al, 2007).…”
Section: Il-10 In Bcg Treatment Of Bladder Cancermentioning
confidence: 99%
“…It has been noted that the development of a dominant Th1 cytokine profile (e.g., IFN-γ, IL-2 and IL-12) is associated with the therapeutic effect of BCG, whereas the presence of a high level of Th2 cytokines (e.g., IL-10) is associated with BCG failure (De Reijke et al, 1996;Saint et al, 2002;Nadler et al, 2003). The kinetic analysis of urinary cytokines indicates that the production of IFN-γ, IL-2 and IL-12 precedes the production of IL-10 in patients undergoing BCG therapy (Nadler et al, 2003).…”
Section: Il-10 In Bcg Treatment Of Bladder Cancermentioning
confidence: 99%